Efficacy of corticosteroid treatment for hospitalized patients with severe COVID-19: a multicentre study. (January 2021) - Bartoletti, Michele; Marconi, Lorenzo; Scudeller, Luigia; Pancaldi, Livia; Tedeschi, Sara; Giannella, Maddalena; Rinaldi, Matteo; Bussini, Linda; Valentini, Ilaria; Ferravante, Anna Filomena; Potalivo, Antonella; Marchionni, Elisa; et al.
Abstract: Objective: To assess the efficacy of corticosteroids in patients with coronavirus disease 2019 (COVID-19). Methods: A multicentre observational study was performed from 22 February through 30 June 2020. We included consecutive adult patients with severe COVID-19, defined as respiratory rate ≥30 breath per minute, oxygen saturation ≤93% on ambient air or arterial partial pressure of oxygen to fraction of inspired oxygen ≤300 mm Hg. We excluded patients being treated with other immunomodulant drugs, receiving low-dose corticosteroids and receiving corticosteroids 72 hours after admission. The primary endpoint was 30-day mortality from hospital admission. The main exposure variable was corticosteroid therapy at a dose of ≥0.5 mg/kg of prednisone equivalents. It was introduced as binomial covariate in a logistic regression model for the primary endpoint and inverse probability of treatment weighting using the propensity score. Results: Of 1717 patients with COVID-19 evaluated, 513 were included in the study, and of these, 170 (33%) were treated with corticosteroids. During hospitalization, 166 patients (34%) met the criteria of the primary outcome (60/170, 35% in the corticosteroid group and 106/343, 31% in the noncorticosteroid group). At multivariable analysis corticosteroid treatment was not associated with lower 30-day mortality rate (adjusted odds ratio, 0.59; 95% confidence interval (CI), 0.20–1.74; p 0.33). After inverse probability of treatment weighting, corticosteroids were not associated with lower 30-day mortality (average treatment effect, 0.05; 95% CI,  −0.02 to 0.09; p 0.12). However, subgroup analysis revealed that in patients with PO2/FiO2 < 200 mm Hg at admission (135 patients, 52 (38%) treated with corticosteroids), corticosteroid treatment was associated with a lower risk of 30-day mortality (23/52, 44% vs. 45/83, 54%; adjusted odds ratio, 0.20; 95% CI, 0.04–0.90; p 0.036). Conclusions: The effect of corticosteroid treatment on mortality might be limited to critically ill COVID-19 patients.